A Comparative Study of L-shaped Multi-storey Building using Rectangular and Special Shaped Columns - Faria Aseem; Dr. D. Rupesh Kumar (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Architects often restrict the widths of the columns so that more free space is available and for the good aesthetic look of the building without columns protruding out of the walls and corners. This is structurally not advisable and economically feasible most of the times hence an alternate solution is required to overcome this difficulty which every structural design engineer faces. Hence non-rectangular special shaped columns have been studied and found out as an alternative to the above said problem since non-rectangular special shaped columns perform better compared to conventional rectangular columns structurally. This study is carried out by considering L-shape building plan with total width of 46.5m and 21m(Y-direction) and total length of 54m (X-direction). A 20 storey building model is analysed with special shaped (L, T,+ Plus) columns and the economical sizes of columns are determined by trial and error with E-Tabs software. Again the same building model is analysed with conventional rectangular columns. The most economical section sizes are obtained by trial and error method to get all columns pass the design criteria and fulfill building drift/deflection and design requirements in compliance with IS 16700-2023, IS456-2000, IS875-2015 and IS1893-2016.After detailed analysis and comparison it is concluded that the L-shape building with special shaped columns performs better under seismic and wind load conditions than the building with conventional rectangular columns under the same loading conditions. The outcome of this study is that the cost of construction of multi-storey buildings like apartments, hotels, offices etc., would be lesser with more free space and column free look if special shaped columns are considered since comparatively smaller size of columns are required than conventional columns with the same size of beams and spans, which contribute to the environment since reduction in construction materials consumption would results in reduction in carbon emission.
Keywords: E-TABS; Special Shaped Columns; Seismic Load; Wind Load; Displacement; Storey Shear; Storey Drift; Base Shear; Overturning Moment